Use of portable Near Infrared Spectroscopy to measure muscle oxygenation and haemodynamics during sports performance - Hesford, C.; Cardinale, M.; Laing, S.; Cooper, C. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The recent development of reliable portable Near Infrared Spectrocopy (NIRS) devices presents the opportunity to non-invasively measure muscle oxygenation and blood flow in-vivo during simulated competition. In short-track speed skating, there is a high anaerobic component (greatly elevated post-race blood lactate concentrations [1]), and high degree of quadriceps deoxygenation [2, 3] due to the sustained nature of muscle contraction, and the ischemic effects of a high level of hip flexion. The local metabolic and haemodynamic response to a short-track race have previously been reported [4], but the effects at local muscle level of skating at different velocities, and using different techniques, are as yet unknown. Subjects were 10 elite short-track speed skaters (6 male, 4 female). Portable wireless NIRS devices (Portamon) were attached to the right and left vastus lateralis (VL) of each subject prior to completion of race simulation time trials (TT). Study design was a randomised crossover; each subject completed TTs over 3 distances: 500m (4.5 laps); 1000m (9 laps); and 1500m (1500m), separated by a minimum of 24 hours. During TT, data relating to Tissue Saturation Index (TSI), and changes in total concentration of haemoglobin (measure of blood volume; considered an indirect measure of blood flow) in the respective muscles was collected at a frequency of 10 Hz. Video recordings of each TT were synchronized with the NIRS-derived data, to permit analysis of blood volume and TSI% changes over the course of individual laps. Global oxygen consumption (VO2) and blood lactate concentration were also monitored. Post-1000m blood lactate was significantly higher than post-500m blood lactate (9.76 ± 0.54 mmol/l v 6.77 ± 0.61 mmol/l, P=0.005) in males, but not in females. Peak VO2 was significantly higher during lap 1 of 500m than lap 1 of 1500m (49.04 ± 5.35 ml•kg-1•min-1 v 31.56 ± 5.24 ml/kg/min, P<0.05). Race distance did not affect magnitude of maximal TSI reduction, in either leg. However, the pattern of blood volume changes in both right and left VL during one lap was shown to be affected by race distance, and therefore mean velocity (Fig 1). Video analysis showed that the differences in the profile of blood volume changes across the three race distances were caused by different techniques employed during cornering when skating at different velocities. The data presented here show that portable NIRS technology has the required temporal resolution to accurately monitor changes in O2 and blood volume in the working muscle during dynamic exercise. This could have a wide range of uses within elite sport, by increasing understanding of the local metabolic effects of changes in technique and velocity.